(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The subject of the study sheds light on the nature of the position of the Russian and Turkish states towards the war on Syria, as the research continues the implications of this War on the positions of those two countries, and follows up and analyzes the causes of these positions and their strategic objectives, and for this the study focused on talking about the stances of Russia and Turkey towards the war on Syria. In addition to the goals and approaches that the two countries have adopted regarding this War, given the geopolitical importance that Syria occupies in the Middle East region, and this matter increased the seriousness of its repercussions on various levels and levels, and the research concludes with important conclusions that are relevant to the nature of the differences and consensus between the two countries on the war on Syria And the effect of intertwining economic interests on setting aside differences over the war on Syria.